Bringing Government into the 21st Century : The Korean Digital Governance Experience - Karippacheril, Tina George (Washington, DC: World Bank, 2016)
This volume—a collaborative work between the World Bank’s Global Governance Practice and a team of researchers working with the Korean Development Institute—is dedicated to the proposition that there is much that can be learned from a careful and nuanced assessment of Korea’s experience with e-governance. It seeks to draw lessons both from the large reservoir of experience as to what has worked, as well as the more limited and isolated examples of what has not. In particular, it seeks to achieve two objectives.